Utilization of addiction treatment among U.S. adults with history of incarceration and substance use disorders - Tsai, Jack (Addict Sci Clin Pract, 2019)
BACKGROUND: The high prevalence of substance use disorders (SUDs) among incarcerated adults in the U.S. is well-known, but there has been less examination of SUD treatment and rates of incarceration among the population of adults with SUDs as the denominator. The current study uses a population-based sample to address three questions: (1) What is the rate of lifetime incarceration among the population of U.S. adults with SUDs?; (2) Among adults with SUDs, what proportion of those with incarceration histories use SUD treatment compared to those without incarceration histories?; and (3) What individual characteristics are associated with utilization of SUD treatment among adults with incarceration histories? METHODS: Data were based on the National Epidemiologic Survey on Alcohol and Related Conditions-III which surveyed a nationally representative sample of U.S. adults through structured interviews. This study focused on the 10,853 respondents who had any lifetime SUD, including 2670 (weighted 22.4%) who reported a lifetime history of incarceration. RESULTS: In the total weighted sample of respondents with SUDs, 22% had been incarcerated before but only 37% had used any alcohol use disorder treatment and 18% had used drug use disorder treatment. Controlling for confounding variables, respondents with SUDs and incarceration histories had 3.1 times the odds of using alcohol use disorder treatment and 1.6 times the odds of using drug use disorder treatment compared to their counterparts with SUDs and no incarceration histories. Having an opioid use disorder, especially heroin use disorder, and a stimulant use disorder, such as cocaine use disorder, had strong associations with any SUD treatment use. CONCLUSIONS: Many U.S. adults with SUDs have histories of incarceration but only a minority use any SUD treatment. Public health approaches that increase access and incentives to engage in and complete SUD treatment may help resolve problems of both incarceration and SUDs in the population.